Human Resource Management of Sub-district Apparatus in Supporting Implementation of Regent's Authority - Hasan Ubadillah; Mochamad Nashrullah (Journal of Business Management and Economic Development, 2026)
This study was conducted with the aim of analyzing the human resource management of local government officials at the sub-district level, focusing on their capacity and competency, using the Human Capital Theory perspective. The delegation of some of the Regional Government's authority to sub-districts is intended to accelerate public service, so that the readiness of the capacity and competency of sub-district officials is very important and strategic in implementing the delegated authority. This study uses a mixed methods method by combining qualitative and quantitative data. The collected data is analyzed descriptively to gain a deep understanding and identify patterns and practices carried out by officials in improving their competence. The results show that in general, sub-district officials have a good level of competence. In terms of technical competence, the level of information technology adoption is relatively high (80.2%), but there is still a skills gap in mastering digital administration systems. In terms of managerial competence, officials demonstrate a high level of responsiveness and speed of decision-making (97.9%), as well as quite effective coordination and team-building skills. Meanwhile, ethical competence is reflected in high levels of trust in organizational policies (97.9%) and conducive working relationships. Education, training, and work experience have been shown to significantly influence the improvement of civil servant competence. This study supports the Human Capital Theory in the public sector by showing that sub-district apparatus' technical, managerial, and ethical competencies support decentralized governance and local government public service delivery.